Biodegradibility Studies of Some Functionalized Imidazolium Ionic Liquids - Munawar b Abdul Hamid, MUNAWAR (Universiti Teknologi Petronas, 2010)
The objectives of the Dissertation of the Final Year Project report is to record all relevant findings from literature reviews regarding the project of biodegradability studies of some functionalized Imidazolium ionic liquids.` Ionic liquids (ILs) are novel organic salts that have enormous potential for industrial use as green replacements for harmful volatile organic solvents. Varying the cationic components can alter the chemical and physical properties of ILs, including solubility, to suit a variety of industrial processes. However, to complement designer engineering, it is crucial to proactively characterize the biological impacts of new chemicals, in order to fully define them as environmentally friendly. We will perform an analysis of the biodegradability of ILs for 28 days by sludge microorganisms collected from the UTP Wastewater Plant using the proper OECD guidelines. We will examine biodegradability of the imidazolium ionic liquids and study the relation between the alkyl chain and the biodegradation. Finally a comparison will be done with Pydridinum ionic liquid to compare the biodegradation of those ionic liquid. From the experiment it can be seen that all the selected ionic liquid have poor biodegradability and it is understood that the longer the chain the poorer the biodegradabilty.Based on the comparison it is clear that imidazolium ionic liquid have poorer biodegradation compared to pyridinum ionic liquid. The release of these ionic liquid to the environment will cause major safety hazard to it. In this work, the attention has been given to data published on the biodegradation of ILs towards aquatic environments and human. The intention of the work is to provide a clear scenario to the reader (in industry and academia) with an understanding of the impact of ILs on the environment.